Analysis of China-Pakistan Cross Border Trade Conflicts Resolution Mechanism - IDREES, Rao Qasim; CHEEMA, Zaheer Iqbal; RIAZ, Jawwad (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020, 2020)
This research paper significantly discusses ‘China Pakistan bilateral investment trade regime’ and the issues relating to dispute settlement as these are considered as high risks to disturb the trade agreements made between Pakistan and China after the huge investment in recent years. Pakistan and China have strong bilateral investment treaty agreements; however, such agreements cannot provide the suitable environment for current bilateral trade and investment, hence required to be amended. In this research authors examine the China Pakistan bilateral investment legal regime and dispute resolution mechanism by way of historical and comparative legal research approaches and considered these as legal risks in the way of foreign investment and the operation difficulties it may encounter. During this study, comparative legal research is applied to find out the differences among Pakistan legal system and international laws to make foreign investment more beneficial. Furthermore, under this research authors maintain the discussion through analytical approach that dispute resolution mechanism prevailing in Pakistan may not be capable to provide required support in favor of Pakistan where international arbitration and trade disputes are still in evolution process and assessed as a barrier in the way of bilateral trade. The objectives of this research are to examine the China Pakistan cross border trade conflict resolution mechanism in depth followed by good social, economic and legal policies for Pakistan. The intention of the researchers through this research is to provide to a stronger, safer and beneficial dispute resolution mechanism towards the socio-economic progress of Pakistan through enhancing the standards of such mechanism.  This research concludes that Free Trade Agreement (FTA) and Bilateral Investment Treaty (BIT) between two countries are obsolete and required many amendments on the account of current investments. To fulfill the objective of current research paper, this study suggests the creation of international commercial court in Pakistan to deal with bilateral investment disputes.